HUBUNGAN PERUBAHAN SUHU TUBUH DENGAN DISABILITAS NEUROLOGIS PADA AKTIVITAS HARIAN PASIEN STROKE ISKEMIK DEFISIT NEUROLOGIS - Belinda Susanto; Poppy Kristina Sasmita; Bryany Titi Santi (PERDOSNI, 2021)
Introduction: Stroke is damage to the brain from interruption of its blood supply caused by an occluded or ruptured blood vessel. Many factors can affect the neurologic outcome, such as body temperature. Higher body temperature has an unfortunate effect on neuron cells’ structure and function. Cell death would increase with increasing exposure to high body temperature.Aim: To determine the relationship between changes in body temperature with neurological deficit in ischemic stroke patients. Methods: This study is a systematic review that uses articles from 2010 to 2020. The search of the articles is conducted by three different databases, ProQuest, PubMed, and Science Direct, with pre-determined keywords. Two researchers reviewed the articles using the Newcastle Ottawa Scale with a maximum score of 9. In the end, six studies are used as the sample of this research. The neurological deficit is scored by the Modified Rankin Scale and the National Institute of Health Stroke Scale (NIHSS) on day 90. Results: Six studies fulfilled the criteria for the literature search and were assessed as having good quality based on NOS. Out of six studies, five studies stated a relationship between the changing of body temperature and neurological deficit in ischemic stroke patients. Only one study stated the opposite. Discussion: This systematic review study shows that there is an association between the changing in body temperature and neurological deficit in ischemic stroke patients, that is, an increase in body temperature can worsen neurological deficit.